Effect of turbinate reduction surgery on allergic rhinitis symptoms in hospitalized patients - Dewa, Yusuf Kusuma; Sardjana, Andriana Tjitria Widi Wardani; Suprijono, Moch. Agus (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2024)
Allergic rhinitis is characterized by nasal congestion, rhinorrhea, sneezing, and itching, significantly impacting patients' quality of life. Turbinate reduction surgery is a therapeutic option for allergic rhinitis refractory to pharmacological treatments. This study aimed to evaluate the effectiveness of turbinate reduction surgery in alleviating allergic rhinitis symptoms. An experimental one-group pretest-posttest design was employed, utilizing primary data collected from 19 patients diagnosed with allergic rhinitis (SFAR = 7) who underwent turbinate reduction surgery at the ENT Clinic, Sultan Agung Islamic Teaching Hospital, Semarang, from April to July 2023. Participants aged 18–55 years were included after providing informed consent. Allergic rhinitis was diagnosed using the Score for Allergic Rhinitis (SFAR), and symptom severity was assessed using the Total Nasal Symptom Score (TNSS). Results showed a significant reduction in the mean TNSS score from 7.79 ± 2.070 pre-surgery to 1.00 ± 0.745 post-surgery (p = 0.000). Scores for allergic rhinitis symptoms also decreased significantly (p < 0.05). These findings suggest that turbinate reduction surgery effectively alleviates allergic rhinitis symptoms in hospitalized patients. Future research should consider larger sample sizes, extended study periods, inclusion of comparison groups, and evaluation of potential surgical complications.